RIP-chip-SRM—a new combinatorial large-scale approach identifies a set of translationally regulated bantam/miR-58 targets in C. elegans - Jovanovic, Marko; Reiter, Lukas; Clark, Alejandra; Weiss, Manuel; Picotti, Paola; Rehrauer, Hubert; Frei, Andreas; Neukomm, Lukas J.; Kaufman, Ethan; Wollscheid, Bernd; Simard, Martin J.; Miska, Eric A.; et al.

(untitled) (Genome Research, 2012)
MicroRNAs (miRNAs) are small, noncoding RNAs that negatively regulate gene expression. As miRNAs are involved in a wide range of biological processes and diseases, much effort has been invested in identifying their mRNA targets. Here, we present a novel combinatorial approach, RIP-chip-SRM (RNA-binding protein immunopurification + microarray + targeted protein quantification via selected reaction monitoring), to identify de novo high-confidence miRNA targets in the nematode Caenorhabditis elegans. We used differential RIP-chip analysis of miRNA-induced silencing complexes from wild-type and miRNA mutant animals, followed by quantitative targeted proteomics via selected reaction monitoring to identify and validate mRNA targets of the C. elegans bantam homolog miR-58. Comparison of total mRNA and protein abundance changes in mir-58 mutant and wild-type animals indicated that the direct bantam/miR-58 targets identified here are mainly regulated at the level of protein abundance, not mRNA stability.